Psychiatry Trainees’ Views of Relational Prescribing: A Mixed Methods Scoping Activity - Haroula Konstantinidou; Joanna Male; Lauren Turner; Dolly Sud (BJPsych Open, 2025)
Aims: Medicine-taking is a complex human behaviour. Psychiatry is returning to the Bio-Psycho-Social paradigm with a re-emphasis on the relational aspects of prescribing. To improve knowledge/understanding of the key concepts of Relational Prescribing, three one-hour seminars each one week apart were delivered to clinicians at Leicestershire Partnership NHS Trust (September 2022). The overall aim was to understand the views of psychiatry trainees.